A Review of Normal Values of Infant Sleep Polysomnography - Daniel K. Ng; Chung-Hong Chan (Elsevier, 2013)
The objective of this study was to summarize current information about the normal values on infant sleep polysomnography for clinical use. Methods: MEDLINE (Ovid), EMBASE (Ovid), and CINAHL (Ovid) from January 1976 to May 2007 were searched. Two reviewers independently reviewed all relevant articles, using preset inclusion criteria. The population of interest included children aged less than 1 year. Studies in infants with known major anomalies were excluded. The results on apneas were extracted and analyzed. Results: For obstructive apnea, the upper limit of normal values was less than 1.0 per hour, and for mixed apnea, the current data suggested the upper limit of normal values was less than 1.0 per hour. For central apnea defined as cessation of respiratory efforts for more than 3 seconds, the current data suggested that the upper limit of the normal central apnea index was 45 per hour for 1-month-old infants, 30 per hour for 2-month-old infants, 22 per hour for 3-month-old infants, and between 10 and 20 for the older age groups. For the desaturation episode defined as SpO2 less than 80% for any length of time, the current data suggested the upper limit of normal values to be 14.7 episodes per hour for day 1, 41 episodes for day 4, and 15.1 episodes for day 39. Conclusion: The normal values of obstructive apnea, mixed apnea, and central apnea are well established for neonates and infants. With these normal values, sleep polysomnography study should be routinely used to quantify the severity of breathing disorders during sleep in those neonates at risk for these disorders.